Organizational culture towards organizational reputation at Employees Provident Fund’s (EPF) headquarters / Tengku Ghazielah Tengku Ghazali - Tengku Ghazali, Tengku Ghazielah (2015)
This paper develops a model of organizational culture based on four traits of organizational culture which are involvement, consistency, adaptability and mission. These traits are examined through the quantitative studies of EPF’s HQ (Head Quarters ) in order to identify their nature of organizational culture towards the organizational reputation at EPF. This study investigates the relationship between organizational culture and organizational reputation. Employing Denision theory, this study collect the data through questionnaires. Questionnaires was developed using literature review. A total of set completed questionnaires were used in the analysis. The findings from the study revealed that Denision’s Cultural traits have significant relationship with organizational reputation at EPF’s HQ. The findings provided a useful tool for organizational culture at EPF’s HQ as it suggest that culture can be studied as an integral part of the adaptation process and the traits can be a useful yardstick for organizational reputation.